Methodology for aligning and comparing spaceborne radar and ground-based radar observations - Bolen, Steven M., author; Chandrasekar, V., author; American Meteorological Society, publisher (Colorado State University. Libraries, 2003)
Direct intercomparisons between space- and ground-based radar measurements can be a challenging task. Differences in viewing aspects between space and earth observations, propagation paths, frequencies, resolution volume size, and time synchronization mismatch between space- and ground-based observations can contribute to direct point-by-point intercomparison errors. This problem is further complicated by geometric distortions induced upon the space-based observations caused by the movements and attitude perturbations of the spacecraft itself. A method to align measurements between these two systems is presented. The method makes use of variable resolution volume matching between the two systems and presents a technique to minimize the effects of potential geometric distortion in space radar observations relative to ground measurements. Applications of the method are shown that make a comparison between the Tropical Rainfall Measuring Mission (TRMM) precipitation radar (PR) reflectivity measurements and ground radar.